Measles susceptibility of marriage migrant women in Korea - Sooyeon Kim; Sun A Kim; Hanbich Hong; Seong Ryeong Choi; Hae-Young Na; Sung Un Shin; Kyung-Hwa Park; Sook In Jung; Min-Ho Shin; Sun-Seog Kweon; Seung Ji Kang (Epidemiology and Health, 2022)
International migrants could be considered a risk group susceptible to vaccine-preventable diseases. We conducted a measles seroprevalence study among 419 marriage migrant women living in Sinan-gun and Wando-gun, South Jeolla Province, located in the southwestern part of Korea. The overall seroimmunity was 92.8%. The seroimmunity varied considerably according to the country of origin and increased with age. Our current analysis could be valuable in the context of discussions concerning vaccination policies for immigrants in Korea.